Gadamer's hermeneutics : between phenomenology and dialectic - Dostal, Robert J. (Northwestern University studies in phenomenology & existential philosophy., 2022)
"This book provides a comprehensive and critical account of Gadamer's hermeneutical philosophy. Robert J. Dostal shows that at the heart of Gadamer's enterprise is the thesis that "being that can be understood is language.""--